Reconstruction of historical riverine sediment production on the goldfields of Victoria, Australia. (March 2018) - Davies, Peter; Lawrence, Susan; Turnbull, Jodi; Rutherfurd, Ian; Grove, James; Silvester, Ewen; Baldwin, Darren; Macklin, Mark
Graphical abstract: Abstract: A significant but previously unquantified factor in anthropogenic change in Australian rivers was the release of large volumes of sediment produced by gold mining in the 19th century. This material, known historically as 'sludge', rapidly entered waterways adjacent to mining areas and caused major environmental damage. We interrogate detailed historical records from the colony of Victoria spanning the period 1859 to 1891 to reconstruct the temporal and spatial distribution of sediment volumes released by mining activity. Based on these records, we estimate that at least 650 million m 3 of material was released into rivers in the 19th century, exceeding natural sediment yield to rivers by an average 140 times. Although the sediment yield per river is not high when compared with examples around the world, the widespread impacts of sludge distinguishes the case of Victoria. The sludge affected three-quarters of catchments in the state due to the large number of small mining operations spread over hundreds of creeks and gullies across the colony. The impacts of sludge to rivers and farmland filled newspapers for more than 50 years and generated numerous parliamentary inquiries. Today, the impacts are largely forgotten and unrecognised, as are the continuing impacts on aquatic systems. The estimates generated in this study provide a basis for understanding the continuing impact of historical mining on Victorian rivers.